Dynamics and cytochemistry of oogenesis in Leporinus striatus Kner (Teleostei, Characiformes, Anostomidae) from the Rio Sapucaí, Minas Gerais State, Brazil - Chini, Helena A.S.; Garcia, José Antônio Dias; Maistro, Edson Luis [UNESP]; Quagio-Grassiotto, Irani [UNESP] (Sociedade Brasileira de Zoologia, 2001)
Oogenesis involves a sequense of transformations which are undergone by female germ cells. These cells change into oogonias and then into mature oocytes. Sexually mature females were collected monthly, during one year, from the Rio Sapucaí, tributary of the Rio Grande, which is part of the Furnas Reservoir system in the state of Minas Gerais. The observed material showed that oogonias were small spherical cells, had a big spherical nucleus, with a single nucleolus, and weakly stained cytoplasm with eosinophilic granules (FG stained), which indicate their protein content. The primary oocytes showed a big basophilic nucleus, with a large peripheral nucleolus, and several smaller nucleoli. They show a reduced cytoplasmic content. The previtellogenic oocytes presented voluminous cytoplasm and nucleus with several small peripheral nucleoli. The oocytes underwent vitellogenesis with the development of the zona radiata and the follicle cells. The zona radiata had two layers, the outer and the inner, which showed its protein content when stained with CM and FG techniques. TB pH 2.5 and pH 4.0 staining showed that oocytes undergoing vitellogenesis presented weakly stained cytoplasm and peripheral cytoplasmic vesicles. The follicle cells that were squamous became cuboidal. In mature oocytes, the yolk granules that filled the cytoplasm became green and blue when stained with FG and CM techniques, indicating their protein content. The perivitclline region showed rosy stained vesicles (TB pH 2.5 and pH 4.0) spread among the weakly stained peripheral vesicles, which seemed to be the cortical alveoli. The zona radiata cells, CM and FG stained, still showed two layers like the oocytes from the previous stage, but thicker.
Keywords: Teleostei; Anostomidae; Leporinus striatus; oogenesis; cytochemical